Plant roots sense soil compaction through restricted ethylene diffusion - Pandey, Bipin K.; Huang, Guoqiang; Bhosale, Rahul; Hartman, Sjon; Sturrock, Craig J.; Jose, Lottie; Martin, Olivier C.; Karady, Michal; Voesenek, Laurentius A. C. J.; Ljung, Karin; Lynch, Jonathan P.; Brown, Kathleen M.; et al. (Science (American Association for the Advancement of Science), 2021)
It's tough to drive a spade through compacted soil, and plant roots seem to have the same problem when growing in compacted ground. Pandey et al. found that the problem is not, however, one of physical resistance but rather inhibition of growth through a signaling pathway. The volatile plant hormone ethylene will diffuse through aerated soil, but compacted soil reduces such diffusion, increasing the concentration of ethylene near root tissues. The cellular signaling cascades triggered by too much ethylene stop root growth. Therefore, gaseous diffusion serves as a readout of soil compaction for plant roots growing in search of productive nutrition. Science , this issue p. 276 Compacted soil restrains diffusion of the volatile plant hormone ethylene, increasing its signal strength and restricting root growth. Soil compaction represents a major challenge for modern agriculture. Compaction is intuitively thought to reduce root growth by limiting the ability of roots to penetrate harder soils. We report that root growth in compacted soil is instead actively suppressed by the volatile hormone ethylene. We found that mutant Arabidopsis and rice roots that were insensitive to ethylene penetrated compacted soil more effectively than did wild-type roots. Our results indicate that soil compaction lowers gas diffusion through a reduction in air-filled pores, thereby causing ethylene to accumulate in root tissues and trigger hormone responses that restrict growth. We propose that ethylene acts as an early warning signal for roots to avoid compacted soils, which would be relevant to research into the breeding of crops resilient to soil compaction.